1222 - Holt, Anne, 1958- (Corvus, 2011)
1222 is the story of how a small group of people find themselves stuck in a hotel during an apocalyptic snow storm.Following a dramatic train derailment at Finse, the conflict between the survivors escalates while a furious hurricane threatens the unprotected village.Nobody is there to help, and there is no way out of the inferno for the survivors hiding out.On the first night at the hotel, a man is found shot and murdered.The victim is Cato Hammer, a priest known nation-wide for his ability - and desire - to get in the papers.Hanne Wilhelmsen, retired Inspector at the Oslo Police, is drawn into a race against time, a murderer, and the worst storm in the Norwegian alps on record.She loses the first round.Soon, another one of God's servants is murdered, when an icicle cuts through his body...